2017
DOI: 10.18632/oncotarget.17357
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nimotuzumab with neoadjuvant chemotherapy followed by concurrent chemoradiotherapy for locoregionally advanced nasopharyngeal carcinoma

Abstract: We assessed the efficacy and safety of nimotuzumab plus neoadjuvant chemotherapy followed by concurrent chemoradiotherapy for Chinese patients with locoregionally advanced nasopharyngeal carcinoma. Clinical data from 210 nonmetastatic nasopharyngeal carcinoma patients diagnosed between May 2008 and April 2014 were retrospectively reviewed. All patients were initially treated with nimotuzumab plus neoadjuvant chemotherapy followed by concurrent chemoradiotherapy. Ninety-five patients received cisplatin-based ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
3
13
0
2
Order By: Relevance
“…Target volumes were delineated according to the recommendations of the International Commission on Radiation Units and Measurements CTV delineation protocol for head and neck malignancies [ 27 , 28 ]. The delineation of NPC target volumes during the IMRT treatment was performed as described previously [ 29 , 30 ]. Gross tumor volume (GTV) referred to the extent of the tumor in clinical and imaging examinations.…”
Section: Methodsmentioning
confidence: 99%
“…Target volumes were delineated according to the recommendations of the International Commission on Radiation Units and Measurements CTV delineation protocol for head and neck malignancies [ 27 , 28 ]. The delineation of NPC target volumes during the IMRT treatment was performed as described previously [ 29 , 30 ]. Gross tumor volume (GTV) referred to the extent of the tumor in clinical and imaging examinations.…”
Section: Methodsmentioning
confidence: 99%
“…Nimotuzumab is an IgG1 humanized monoclonal antibody directed against the extracellular domain of the EGFR blocking the binding to its ligands. Several studies demonstrated that nimotuzumab combined with neo-adjuvant chemotherapy or concurrent chemotherapy brings overall survival bene t [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent radical IMRT with simultaneous integrated boost technique using 6 MV photons within 2-3 weeks after IC. Target volumes of NPC during IMRT treatment were delineated as described previously [ 25 , 30 33 ]. Briefly, gross tumor volumes (GTV) of the primary tumor (GVTnx) and metastatic lymph nodes (GTVnd) were delineated according to pre- and post-IC MR images, respectively.…”
Section: Methodsmentioning
confidence: 99%